Impact of Essential Oils Obtained from Safflower Stem and Roots on Germination and Seedling Growth of Wheat, Barley, Sunflower and Chickpea - Sibel Day (Turkish Journal of Agriculture: Food Science and Technology)
The phytotoxic impact of safflower extracts prepared by different plant parts like stem and root of it on germination and seedling growth of plants like wheat (Triticum aestivum L.), barley (Hordeum vulgare L.) sunflower (Helianthus annuus L.) and chickpea (Cicer arietinum L.) were studied. Root and stem extracts of safflower at 2.5, 5 and 10% concentrations were obtained from safflower residuals after harvest of the plants. Mean germination time and percentage, root and shoot length, fresh and dry weight of seedlings were investigated. Essential oil composition of both root and stem extracts were determined. Results indicated that extract doses significantly influenced mean germination time of sunflower and chickpea. Germination time of wheat and barley also decreased with the increasing extract doses. The other growing parameters of all crops were also decreased with extract doses. The main essential oil compound of root extract was 1-Pentadecene (47.78%) followed by 2-Naphthalenemethanol (33.07%). The main essential oil compound of stem extract was 2-Naphthalenemethanol (49.15%) followed by Lauryl alcohol (22.26%). Root and stem extracts of safflower showed different effects. Stem extract mostly had severe impact on sunflower while root extract had this impact on wheat and barley. Consequently, removing stem parts of the safflower from field could reduce the amount of secondary metabolites released from the plant parts.